2022
DOI: 10.3390/plants11223143
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina platensis Ameliorates Oxidative Stress Associated with Antiretroviral Drugs in HepG2 Cells

Abstract: Lately, Spirulina platensis (SP), as an antioxidant, has exhibited high potency in the treatment of oxidative stress, diabetes, immune disorder, inflammatory stress, and bacterial and viral-related diseases. This study investigated the possible protective role of Spirulina platensis against ARV-induced oxidative stress in HepG2 cells. Human liver (HepG2) cells were treated with ARVs ((Lamivudine (3TC): 1.51 µg/mL, tenofovir disoproxil fumarate (TDF): 0.3 µg/mL and Emtricitabine (FTC): 1.8 µg/mL)) for 96 h and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…This study reveals that ARVs negatively regulate the NRF2 pathway. Similar to our study, Similar to our study, Sibiya, Ghazi [ 90 ] showed a significant decrease in NRF2 and pNRF2 protein expression in HepG2 cells treated with ARV drugs (TDF and 3TC). Singh, Kotla [ 91 ] showed that the HAART (containing TDF and FTC) increased monocyte/macrophage sensitivity to ROS in HIV + individuals by suppressing NRF2-ARE activity via p90RSK-mediated ERK5 S496 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…This study reveals that ARVs negatively regulate the NRF2 pathway. Similar to our study, Similar to our study, Sibiya, Ghazi [ 90 ] showed a significant decrease in NRF2 and pNRF2 protein expression in HepG2 cells treated with ARV drugs (TDF and 3TC). Singh, Kotla [ 91 ] showed that the HAART (containing TDF and FTC) increased monocyte/macrophage sensitivity to ROS in HIV + individuals by suppressing NRF2-ARE activity via p90RSK-mediated ERK5 S496 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Following 120 h of treatment, protein was isolated and standardised as per Sibiya et al, 2022 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following treatment, RNA isolation and standardisation was performed as per Sibiya et al, 2022 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells were used, as they mimic the physiological functions and epigenetic profiles of primary hepatocytes [ 27 ]. Additionally, they have commonly been used as in vitro models for studies assessing ARV toxicity [ 28 , 29 , 30 ]. Following an extensive review of the literature, a treatment period of 120 h (h) was selected to assess the chronic effects of ARVs in HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%